2015
DOI: 10.1136/oemed-2014-102412
|View full text |Cite
|
Sign up to set email alerts
|

Extended follow-up of lung cancer and non-malignant respiratory disease mortality among California diatomaceous earth workers

Abstract: The risk of lung cancer and NMRD mortality remained elevated, although generally non-significant, and exposure-response trends with cumulative crystalline silica persisted on extended follow-up of this cohort. The findings support a generally consistently observed aetiological relation between crystalline silica and lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Although smoking information was available for 50% of the workers in the present study, information on smoking intensity or duration were not available; thus we relied on ever/never-smoker classification for confounding control. Smoking should certainly be considered a common cause of both events of interest (as well as all-cause mortality) and also appears to be a positive confounder in this cohort (4). Inability to fully adjust for smoking could result in potential residual confounding.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although smoking information was available for 50% of the workers in the present study, information on smoking intensity or duration were not available; thus we relied on ever/never-smoker classification for confounding control. Smoking should certainly be considered a common cause of both events of interest (as well as all-cause mortality) and also appears to be a positive confounder in this cohort (4). Inability to fully adjust for smoking could result in potential residual confounding.…”
Section: Discussionmentioning
confidence: 93%
“…Work histories and silica exposure assessments were available from the beginning of plant operations (1902 for one plant and 1946 for the other) through 1994. Mortality follow-up was based on data from the National Death Index, state driver’s license bureaus, and commercial credit bureaus (4) and was available from January 1, 1942, to December 31, 2011, for a maximum follow-up time of 70 years. Complete mortality follow-up was not available for 183 participants.…”
Section: Methodsmentioning
confidence: 99%
“…(IARC, 2012) Besides silicosis and lung cancer, cumulative low level exposure to RCS increases the risk of other non-malignant respiratory diseases including chronic obstructive pulmonary disease, bronchitis and emphysema and possibly non-malignant renal disease. (Steenland, 2005, Gallagher et al, 2015, Rushton, 2007, McDonald et al, 2005 The main source of RCS exposure is occupational. Internationally, the established occupations with high exposure are sandblasters, miners, millers, ceramics workers, glassmakers, quarry workers, sand/stone grinding workers, and casting, shakeout or blasting workers.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported on the association between exposure to respirable crystalline silica (RCS) and adverse health effects, including silicosis, lung cancer, non-malignant respiratory disease, and possibly kidney disease [ 1 , 2 , 3 , 4 , 5 ]. The International Agency for Research on Cancer (IARC) reviewed the scientific literature and designated crystalline silica (i.e., quartz, cristobalite, and tridymite) as a Group 1 human carcinogen [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%